Assessment of rice sheath rot disease risk for its establishment in Southern Coastal states of India - C, Vimalkumar; Das, Bappa; K, Sathiyaseelan; Venu, E; SM, Manu; Sinha, P (ORYZA-An International Journal of Rice, 2023)
Rice sheath rot (Sarocladium oryzae) is an emerging disease in all rice ecosystems and considered as one of the major threats to rice production. For development of precise management strategies spatial distribution of infection risk is essential to ascertain epidemic nature of the disease. For risk estimation, temperature-based infection model has been designed and disease risk estimated as the monthly cumulative value of the daily infection index. Geo-spatial distribution of infection risk has been assessed for the coastal rice ecosystems based on 39 years of weather data and two years (2018 and 2019) of surveyed ground truth. Infection risk was noted to be higher in kharif than rabi season and the eastern coast was identified as hotspot. Yearly variation estimates has indicated rabi rice is likely to be vulnerable to climate change arising due to temperature rise. Infection risk prediction based on critical weather factor is useful in germplasm, fungicide evaluation along with development of management strategies.